Vergleichsstudie zur Ausdrucksstärke von SMT-Solvern - Engelbrecht, Marco

Unlinkable content playbacks in a multiparty DRM system - Petrlic, Ronald; Sekula, Stephan (Data and Applications Security and Privacy XXVII)
We present a solution to the problem of privacy invasion in a multiparty digital rights management scheme. (Roaming) users buy content licenses from a content provider and execute it at any nearby content distributor. Our approach, which does not need any trusted third party - in contrast to most related work on privacy-preserving DRM - is based on a re-encryption scheme that runs on any mobile Android device. Only a minor security-critical part needs to be performed on the device's smartcard which could, for instance, be a SIM card.

Two-Stage Allocation Procedures - Röhl, Nils
Suppose some individuals are allowed to engage in different groups at the same time and they generate a certain welfare by cooperation. Finding appropriate ways for distributing this welfare is a non-trivial issue. The purpose of this work is to analyze two-stage allocation procedures where first each group receives a share of the welfare which is then, subsequently, distributed among the corresponding members. To study these procedures in a structured way, cooperative games and network games are combined in a general framework by using mathematical hypergraphs. Moreover, several convincing requirements on allocation procedures are discussed and formalized. Thereby it will be shown, for example, that the Position Value and iteratively applying the Myerson Value can be characterized by similar axiomatizations.

Towards practical privacy-preserving Digital Rights Management for Cloud Computing - Joshi, Nakul; Petrlic, Ronald (Proceedings of the 10th Annual IEEE Consumer Communications & Networking Conference (CCNC))
We propose a privacy-preserving digital rights management scheme for (future) cloud computing. Users buy software from software providers and execute it at computing centers. Our solution allows software providers to provide different license models, like execute at most n-times models. Users’ anonymity and unlinkability of actions are preserved and thus, profile building is not even possible under (a) pseudonym. Privacy protection in the honest-but-curious model is achieved by combining ring signatures with an anonymous recipient scheme.We employ secret sharing in a unique manner that allows the software provider to expose the user’s identity if the user commits fraud, e.g. by exceeding the execution limit n.

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Three-Valued Abstraction and Heuristic-Guided Refinement for Verifying Concurrent Systems - Timm, Nils
Software systems are playing an increasing role in our everyday life, and as the amount of software applications grows, so does their complexity and the relevance of their computations. Software components can be found in many systems that are charged with safety-critical tasks, such as control systems for aviation or power plants. Hence, software verification techniques that are capable of proving the absence of critical errors are becoming more and more important in the field software engineering. A well-established approach to software verification is model checking. Applying this technique involves an exhaustive exploration of a state space model corresponding to the system under consideration. The major challenge in model checking is the so-called state explosion problem: The state space of a software system grows exponentially with its size. Thus, the straightforward modelling of real-life systems practically impossible. A common approach to this problem is the application of abstraction techniques, which reduce the original state space by mapping it on a significantly smaller abstract one. Abstraction inherently involves a loss of information, and thus, the resulting abstract model may be too imprecise for a definite result in verification. Therefore, abstraction is typically combined with abstraction refinement: An initially very coarse abstract model is iteratively refined, i.e. enriched with new details about the original system, until a level of abstraction is reached that is precise enough for a definite outcome. Abstraction refinement-based model checking is fully automatable and it is considered as one of the most promising approaches to the state explosion problem in verification. However, it is still faced with a number of challenges. There exist several types of abstraction techniques and not every type is equally well-suited for all kinds of systems and verification tasks. Moreover, the selection of adequate refinement steps is nontrivial and typically the most crucial part of the overall approach: Unfavourable refinement decisions can compromise the state space-reducing effect of abstraction, and as a consequence, can easily lead to the failure of verification. It is, however, hard to predict which refinement steps will eventually be expedient for verification – and which not.

The Impact of Individual and Collective Reputation on Wine Prices: Empirical Evidence from the Mosel Valley - Frick, Bernd; Simmons, Robert (Journal of Business Economics)
Although of considerable practical importance, the separate impact of individual and collective reputation on firm performance (e.g. product prices) has not yet been convincingly demonstrated. We use a sample of some 70 different wineries offering more than 1,300 different Riesling wines from the Mosel valley to isolate the returns to individual reputation (measured by expert ratings in a highly respected wine guide) from the returns to collective reputation (measured by membership in two different professional associations where members are assumed to monitor each other very closely). We find that both effects are statistically significant and economically relevant with the latter being more important in quantitative terms than the former.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Statistisches Planen von Aktionen für autonome mobile Roboter in realen Umgebungen - Bieshaar, Maarten

SimuLizar: Design-Time modeling and Performance Analysis of Self-Adaptive Systems - Becker, Matthias; Becker, Steffen; Meyer, Joachim (Proceedings of the Software Engineering Conference (SE))
Modern software systems adapt themselves to changing environments, to meet quality-of-service requirements, such as response time limits. The engineering of the system’s self-adaptation logic does not only require new modeling methods, but also new analyzes of transient phases. Model-driven software performance engineering methods already allow design-time analysis of steady states of non-adaptive system models. In order to validate requirements for transient phases, new modeling and analysis methods are needed. In this paper, we present SimuLizar, our initial model-driven approach to model self-adaptive systems and analyze the performance of their transient phases. Our evaluation of a load balancer toy example shows the applicability of our modeling approach. Additionally, a comparison of our performance analysis with a prototypical implementation of our example system shows that the prediction accuracy is sufficient to identify unsatisfactory self-adaptations.

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Semi-Automated Software Composition Through Generated Components - Mohr, Felix; Kleine Büning, Hans (Proceedings of the 15th International Conference on Information Integration and Web-based Applications & Services (iiWAS))
Software composition has been studied as a subject of state based planning for decades. Existing composition approaches that are efficient enough to be used in practice are limited to sequential arrangements of software components. This restriction dramatically reduces the number of composition problems that can be solved. However, there are many composition problems that could be solved by existing approaches if they had a possibility to combine components in very simple non-sequential ways. To this end, we present an approach that arranges not only basic components but also composite components. Composite components enhance the structure of the composition by conditional control flows. Through algorithms that are written by experts, composite components are automatically generated before the composition process starts. Therefore, our approach is not a substitute for existing composition algorithms but complements them with a preprocessing step. We verified the validity of our approach through implementation of the presented algorithms.

Growing existing customers' revenue streams through customer referral programs - Garnefeld, Ina; Eggert, Andreas; Helm, Sabrina V; Tax, Stephen S (Journal of Marketing)

Erfolgsfaktor Value-Based Selling—Verkaufen, wenn Kundenorientierung nicht zum Erfolg führt - Haas, Alexander; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang (Marketing Review St. Gallen)

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Individual determinants of work attendance: Evidence on the role of personality - St{\, Susi; Fahr, Rene (Applied Economics)

Scheduling Variants with Speed-Scaling via the Primal-Dual Approach - Knopf, Michael